The state of anti-toxin post-vaccinal immunity in children with allergic diseases (atopic dermatitis) in Volgograd - E. B. Belan; E. M. Nikiforova; A. A. Panina; T. L. Sadchikova; T. V. Samofalova (Аллергология и Иммунология в Педиатрии)
The postvaccination immunity to bacterial toxins in preschool-age children with atopic dermatitis before the second revaccination has been studied. It was determined that protective immunity against Cl. tetani toxin is kept in 100% cases and against C. diphtheriae in 86,7% ones. High level of antitoxic IgG is detected in more than half of all children.